Relaxed dignity: KAAN designs new building for Tilburg University (OverHolland, 2018)
‘KAAN Architecten and the building firm VORM are together creating a large new building on the Tilburg University campus. With 11,000 square metres of floor area, the university’s Teaching and Self-Study Centre (OZC) is intended to offer students better facilities and hence further improve the quality of education. The building will have BREEAM (Building Research Establishment Environmental Assessment Method) ‘Excellent’ certification, the maximum achievable level of sustainability. Completion is scheduled for autumn 2017. The KAAN Architecten design shows an OZC that is square and fairly low, like various other buildings on the campus. This means it will fit in well among the trees and the other buildings. Yet it is substantially different from the square central Cobbenhagen building, the former Catholic College of Economics that formed the basis for the university back in the early 1960s. Whereas with its two courtyards the enclosed structure by architect Jos. Bedaux (1910-1989) brought the landscape inside the building, KAAN Architecten’s centre will blend into it. Abundant daylight and radical perspectives will allow the building and its surroundings to merge. The study areas will be enclosed in the same way as a woodland clearing.